Waves and information transfer - Hudak, Heather C., 1975- (St. Catharines, Ontario : Crabtree Publishing Company, 2017)
Explores how light and sound waves transfer information. From telescopes that extend our sense of sight to satellites that help us communicate across large distances, patterns of waves transfer information in many ways.
Waves in motion -- Patterns of information -- Information waves -- Waves in time -- Looking for new solutions -- Innovations in wave technology -- Living in a digital world -- Digitizing the data around us -- Waves and your devices -- Wireless waves -- Sending messages with waves -- Create your own electrical device -- Create your own code -- What happened and why?
Includes bibliographical references (page 31) and index.
6.9
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Electromagnetic waves -- Juvenile literature; Wave mechanics -- Juvenile literature; Information technology -- Juvenile literature; Electromagnetic waves; Wave mechanics; Information technology